AB0179 An innovative histological classification of rheumatoid synovitis and its relationship to clinical disease activity and joint destruction. (23rd January 2014) - Mo, Y.-Q.; Ma, J.-D.; Chen, L.-F.; Zheng, D.-H.; Zhu, L.-J.; Dai, L.
Abstract : Background: Rheumatoid arthritis (RA) is a heterogeneous disease and subtyping of RA may help optimal therapeutic strategies and outcome prediction. However, there has been no available satisfying classification method till now. Synovium is the target tissue involved in RA and it is potential to classify RA patients according to synovitis type. Recently, normal synovium was reported to be well-defined into areolar, fibrous and fatty types (Kelley's Textbook of Rheumatology, 8 th edition). Here we set up an innovative histological classification of rheumatoid synovitis. Objectives: To explore the relationship of histological classification of rheumatoid synovitis with clinical disease activity and joint destruction. Methods: Synovial tissue was obtained by needle biopsy from inflamed knees of 152 consecutive patients with active RA and stained with H&E. Histological synovitis was divided into three types according to the major components of subintima: (1) Areolar (A) synovitis: mainly composed of collagenous tissue or loose connective tissue, with cellular loose fibrovascular fatty structure; (2) Fibrous (Fi) synovitis: mainly composed of dense connective tissue or fibrous tissue, with poorly vascularized structure; (3) Fatty (Fa) synovitis: abundant mature adipose tissue with little collagen deposition. Kruskal-Wallis ranks test was used to compare the difference of clinical characteristics among three groups. Results: (1) Among 152 RA patients, 128 (84%) were female, median age was 52 years (range 23 80) and median disease duration was 42 months (range 3 480). (2) As shown in Figure 1, 27 (18%) RA patients had A type synovitis, 98 (64%) had Fi type and 18 (12%) had Fa type; while 9 (6%) patients had more than one types (7 patients had A+Fa type; 2 patients had Fi+Fa type). (3) 143 patients with unique synovitis type were divided into three groups. There was significant difference of disease duration, CRP, ESR, DAS28-crp, DAS28-esr, SDAI, RF among three groups (all p <0.05). ESR, DAS28, SDAI and RF in Fi group were significantly higher than that in A group (all p <0.017). CRP in Fi group was significantly higher than that in Fa group (χ 2 =7.619, p =0.006). Disease duration in Fa group was significantly shorter than that in Fi group (χ 2 =9.729, p =0.002) or A group (χ 2 =11.862, p =0.001). (4) Sharp narrowing score, erosive score and total score showed significant difference among three groups (all p <0.001). All Sharp scores in A group were significantly higher than that in Fi group (all p <0.017), and all Sharp scores in Fi group were higher than that in Fa group (all p <0.017). Image/graph: Conclusions: Our study proposed an innovative histological classification of rheumatoid synovitis based on the major components of synovial subintima and suggested higher clinical disease activity in RA patients with Fi type syovitis, and severer joint destruction in patients with A type synovitis. Acknowledgements: This work was supported by the Chinese National Natural Science Research Grant (grant no. 30972742 and 81001334), the Natural Science Research Grant of Guangdong Province, China (grant no. 9151008901000130 and 10451008901004542) and the Fundamental Research Funds for the Central Universities (no. 10ykpy19). Disclosure of Interest: None Declared